2004
DOI: 10.1038/sj.gt.3302300
|View full text |Cite
|
Sign up to set email alerts
|

Sequential delivery of interferon-α gene and DCs to intracranial gliomas promotes an effective antitumor response

Abstract: Effective presentation of tumor antigens by dendritic cells (DCs) is considered to be essential for the induction of antitumor T-cell responses. Apoptotic and necrotic tumors have been noted to be a robust antigen source for DCs. Because glioma cells undergo apoptosis after transfection with the type I interferon (IFN) gene and type I IFNs promote the stimulatory activity of DCs, we hypothesized that transfection of glioma cells with type I IFN genes and provision of DCs would promote particularly effective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…IFN-inhibits cell cycle progression and induces apoptosis in tumor cells thereby leading to enhanced immune system reaction by increasing expression of MHC-1 (King 2005 andYang 2004). IFN-has shown to regress glioma in animal model when co-delivered with DCs into the tumor (Tsugawa 2004).…”
Section: Immuno Gene Therapymentioning
confidence: 99%
“…IFN-inhibits cell cycle progression and induces apoptosis in tumor cells thereby leading to enhanced immune system reaction by increasing expression of MHC-1 (King 2005 andYang 2004). IFN-has shown to regress glioma in animal model when co-delivered with DCs into the tumor (Tsugawa 2004).…”
Section: Immuno Gene Therapymentioning
confidence: 99%
“…Scherr et al (2005) used HIV vectors to investigate the potential therapeutic applications of RNAi as stable gene transfer systems for K562 cancer cell lines and for CD34+ cells from chronic myeloid leukemia patients and have shown that stable RNAi may represent an useful approach to cancer gene therapy. Not only HIV-based vectors have been evaluated in this context, with for instance, adeno-associated vectors having been used in intratumoral injection in order to promote antitumor response (Tsugawa et al, 2004). However, it seems more appropriate to employ a viral vector able to induce immune responses which constitute by themselves a therapeutic approach for cancer.…”
Section: Applications Of Hiv-based Vectorsmentioning
confidence: 99%
“…Therefore, the combined use of DC-based immunotherapy with IFN-a gene therapy is considered reasonable. Recently, Tsugawa et al 30 reported that combined use of DC with adenoviral vector encoding IFN-a elicits antitumor response in a murine intracranial gliomas model. In this study, as a preliminary investigation of the combined therapy, we investigated the effects of bone marrow-derived DCs and IFN-a-expressing colorectal cancer cells on the proliferation of allogeneic splenocytes.…”
Section: Introductionmentioning
confidence: 99%